Invent & wander : the collected writings of Jeff Bezos. - Bezos, Jeffrey (Boston, Massachusetts : Harvard Business Review Press & Public Affairs, 2021)
A collection of writings by the founder and CEO of Amazon includes a selection of Bezos's unusual annual shareholder letters, speeches, and interviews that offer insight into his background, his professional approaches, and the evolutions of his ideas.
Keywords: Bezos, Jeffrey; Amazon.com (Firm); Entrepreneurship; Book industries and trade -- United States; Creative thinking; Success